Literature Study of The Influence of Big Data and Data Analytic on Cost Controls - Titis Wahyuni (Proceedings, 2023)
Cost control is very important for companies in the era of big data because the cost is the main factor affecting a company’s competitiveness. This study aims to examine the impact of big data and data analytics on cost control in companies. This qualitative research uses the literature review method to better understand the influence of big data and data analytics (BDA) on cost control in the company. The results of the study revealed that, with the rapid development of information technology, the integration between data analytics and big data can effectively increase the competitiveness of the company’s market.